“Death Drive, Martyrdom, and Deathbed Scenes. The Narration of Death in Harriet Wilson’s Autobiographical Novel” - Karima ZAARAOUI (E-REA)
This paper examines the autothanatographical occasion(s) in Harriet Wilson’s autobiographical novel. Published without anyone noticing in 1859 and resuscitated in 1981, Our Nig; or, Sketches in the Life of a Free Black, North first appears as a commercial failure but most importantly as a voice coming from the vault. From a narratological point of view, the plot hinges on characters’ deathbed scenes and premature deaths or death wishes, culminating in a performance of death. In light of Aristotle’s definition of tragedy, this article proposes to read Our Nig as a profound meditation on death, race and God. Wilson as an autothanatographer, genuinely enacts her own death through her writing project. Against all odds, her project will go beyond its object in an ultimate “death-defying act” (Thomas Couser).